2020
DOI: 10.1177/1847980420982119
|View full text |Cite
|
Sign up to set email alerts
|

Multi-response optimization of chromium/gold-based nanofilm Kretschmann-based surface plasmon resonance glucose sensor using finite-difference time-domain and Taguchi method

Abstract: Kretschmann-based surface plasmon resonance sensor utilizing chromium and gold nanofilms is ideal for label-free biomedical sensing. In this work, Taguchi’s L9 orthogonal array method was used to optimize the effects of three control factors and noise factor, which are the incident optical wavelength, chromium and gold nanofilm thicknesses, and their root-mean-square surface roughness, on the performance of the Kretschmann-based surface plasmon resonance sensor. The control factors were varied at three levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 61 publications
(79 reference statements)
0
9
0
Order By: Relevance
“…For the materials database, the refractive index of BK7, Au and Cr are taken from BioNavis [ 26 , 42 ] and the refractive index of ZnO is obtained from Stelling [ 26 , 43 ]. Meanwhile the RI of uric acid at different concentrations of 0 mM–3.0 mM were obtained from Gan et al [ 11 ] with RI of 1.333, 1.3331, 1.3332, 1.3334, 1.3335, and 1.3336, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…For the materials database, the refractive index of BK7, Au and Cr are taken from BioNavis [ 26 , 42 ] and the refractive index of ZnO is obtained from Stelling [ 26 , 43 ]. Meanwhile the RI of uric acid at different concentrations of 0 mM–3.0 mM were obtained from Gan et al [ 11 ] with RI of 1.333, 1.3331, 1.3332, 1.3334, 1.3335, and 1.3336, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Another bimetallic Ag (30nm)/Au (17.5nm) thin film based SPR glucose sensor was reported by Mulyanti et al [158] that showed sensitivity and figure of merit values of 4.7993°/RIU and 0.5173 at 633 nm incident wavelength for a glucose concentration of 0.08 g/dl. Most recently, other multi-layer, e.g., chromium/gold [159], Ag/Si3N4/Au [160], and SiO2 /gold/silver [161] thin film based SPR biosensors have shown excellent performances in the detection of glucose in blood or glucose/water solutions. Notably, different methods, including Taguchi method, FDTD simulation, COMSOL simulation, were used in such works to optimize the sensor design considerations.…”
Section: Analysis Of Lipid/protein Moleculesmentioning
confidence: 99%
“…The Taguchi method is used as an efficient and frugal design method that is scientific and practical in exploring the optimal state. It is a special design method which reduces the number of tests by utilizing mathematical fundamentals [ 13 , 14 , 15 ]. Liu et al [ 16 ] established a multi-body dynamic model of a suspended monorail vehicle.…”
Section: Introductionmentioning
confidence: 99%